Acceptability of sufficiency consumption policies by Finnish households - Nuorivaara, Essi; Ahvenharju, Sanna (Ubiquity Press, Ltd., 2025)
Sufficiency policies aim to decrease and avoid the demand for energy, materials, land and water. This research examines the acceptability of sufficiency consumption policies among Finnish households and how Finnish households experience sufficiency as a guiding principle specificallyfor sustainable energy consumption. The research questions are: (1) In what ways do the Finnish households find the proposed sufficiency policies acceptable? (2) How do the Finnish households justify their position towards the sufficiency policies? (3) How do the circumstances of households influence the acceptance of sufficiency measures? Qualitative semi-structured household interviews (n = 39) were conducted in 2023. Participants were asked to evaluate acceptability and feasibility of sufficiency policy measures. The results show that the principle of sufficiency was generally well-received by the households and the policies were generally found acceptable under certain conditions. Exceptions were the two hardest policies: higher income tax and restricting the size of living space. However, the acceptability of the different policy measures varied notably between individuals, which suggests that it would be important to tailor policies to different contexts and target groups.